DEVELOPMENT OF BIPOLAR ELECTRODE MODELS FOR EFFEC-TIVE HEAT DISTRIBUTION DURING RADIOFREQUENCY ABLATION OF VARICOSE VEINS - Solovyov, V. G.; Lankin, Yu. M.; Romanova, I. Yu. (Medical Informatics and Engineering, 2023)
Background. The research is devoted to modeling the design of bipolar elec-trodes for effective heat distribution during radiofrequency ablation of varicose veins. Materials and methods. Mathematical modeling of the distribution of heat fields during vein ablation was carried out for three designs of ablators and the best in terms of the uniformity of the distribution of the heat field along the electrode was found. Results. Three variants of designs of bipolar electrodes for RFA are considered. The variant of the ablator with an electrode in the form of a bipolar wire winding with a rectangular section around the insulator is more acceptable from the point of view of the uniformity of the distribution of the thermal field along the electrode. Temperature control of biological tissue using data on the functional dependence of the specific conductivity of biological tissue on temperature can be applied only until structural changes in the tissue are achieved, after which the process of temperature control is complicated. If it is impossible to maintain the set temperature for the required time, the thermal capacity of the insulator can be used as an additional source of heat. To do this, after reaching the set temperature of the inner surface of the vein, the voltage is turned off, but the heat from the insulator and electrodes is transferred to the wall of the vein, which leads to heating of the inner surface of the vein and partial cooling of its outer surface. Conclusions. The maintenance of the given temperature distribution is decided by the selection of appropriate materials with the given coefficient of thermal conductivity and heat capacity, the choice of the value of the supply voltage and the geometrical parameters of the electrode. In the case of uneven distribution of the thermal field in the control zone and the appearance of areas with structural changes in the tissue, such areas can acquire unpredictable properties of the functional dependence of the specific conductivity of biological tissue on temperature. In such cases, the use of a stabilized voltage source can help, as the voltage will be redistributed between the areas, equalizing the heating and allowing to achieve positive results when heating the biological tissue.